INVESTIGATING CONCURRENT LECTURER PERFORMANCE: THE ROLE EFFORT AS MEDIATION & TASK COMPLEXITY AS MODERATION - Helmi Yazid; Lili Sugeng Wiyantoro; Iis Ismawati (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2023)
Currently, there are most accounting graduates who have not been able to compete to fill jobs in their fields. Universities must address it immediately. This study investigates the effect of the performance of university accounting lecturers in Jakarta – Banten. This study used respondents 334 of academics and auditors at universities in Jakarta and Banten. Sampling using purposive sampling method, and data analysis method using SEM. This research shows that accountability, self-ability, and effort can affect the performance of audit lecturers who also act as auditors. Then, complexity proved capable of being a moderation variable and Effort proved capable of being a mediation variable. This study explains that lecturers as academics and concurrently as auditors at universities in Jakarta and Banten who have high confidence will make maximum efforts to improve lecturer performance so that it will have an impact on decision making and be able to do their jobs well.